2013
DOI: 10.1631/jzus.bqicc706
|View full text |Cite
|
Sign up to set email alerts
|

A correlation between acute kidney injury and myonecrosis after scheduled percutaneous coronary intervention

Abstract: Slight elevations in cardiac troponin I and T are frequently observed after percutaneous coronary intervention (PCI). Contrast-induced acute kidney injury (CI-AKI) is a complex syndrome induced by exposure to intravascular contrast media (CM). Currently, the relationships between the CM, pre-existing kidney insufficiency, CI-AKI, and myonecrosis after elective PCI are unclear. To investigate the relationship between CI-AKI and post-procedural myonecrosis (PMN) after PCI, we analyzed 327 non-ST-segment elevatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Previous studies that evaluated the predictors of post-PCI myocardial damage found that the contrast volume may be associated with myocardial injury (defined by 1 × ULN or above 20% of the initially positive). 10,24,25) Griva, et al 24) found that a positive correlation between cTnI levels and the amount of the contrast medium injected into the coronary arteries in patients underwent coronary angiography (CAG) without intervention. A similar conclusion was reported by Abu Sharar, et al, 26) 0.3% of cases had the cTnT peak levels after CAG meeting criteria of PMI according to the third version of the universal MI definition.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that evaluated the predictors of post-PCI myocardial damage found that the contrast volume may be associated with myocardial injury (defined by 1 × ULN or above 20% of the initially positive). 10,24,25) Griva, et al 24) found that a positive correlation between cTnI levels and the amount of the contrast medium injected into the coronary arteries in patients underwent coronary angiography (CAG) without intervention. A similar conclusion was reported by Abu Sharar, et al, 26) 0.3% of cases had the cTnT peak levels after CAG meeting criteria of PMI according to the third version of the universal MI definition.…”
Section: Discussionmentioning
confidence: 99%